2018
DOI: 10.17843/rpmesp.2018.351.3603
|View full text |Cite
|
Sign up to set email alerts
|

Prácticas culturales vinculadas al cuidado de la salud y percepción sobre la atención en establecimientos de salud en residentes de centros poblados alto-andinos de Huancavelica, Perú

Abstract: Inequalities in terms of access and quality of healthcare persist, especially among Andean populations, such as the community of Chopcca. Here, we describe the perception of healthcare provided in medical facilities as well as the practices linked to health care in residents of settlements in the Huancavelica region. We carried out a cross-sectional study by means of a structured questionnaire administered to 775 residents of urban and rural towns of the Yauli and Paucará districts. 68.7% refer always using me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
0
6
0
9
Order By: Relevance
“…Concerning the use of other substances, it was found that the use of medicines and medicinal plants to prevent COVID-19 was associated with higher consumption of chlorine dioxide as a preventive measure. The use of medicinal plants [39] and self-medication are common practices in Peru, especially during the pandemic [21]. However, the fact that people consume one of these measures does not mean that they trust in its efficacy [40] leading them to seek more than one preventive measure such as medicines and to rely on pseudoscientific beliefs such as the consumption of chlorine dioxide [36].…”
Section: Factors Associated With Chlorine Dioxide Consumptionmentioning
confidence: 99%
“…Concerning the use of other substances, it was found that the use of medicines and medicinal plants to prevent COVID-19 was associated with higher consumption of chlorine dioxide as a preventive measure. The use of medicinal plants [39] and self-medication are common practices in Peru, especially during the pandemic [21]. However, the fact that people consume one of these measures does not mean that they trust in its efficacy [40] leading them to seek more than one preventive measure such as medicines and to rely on pseudoscientific beliefs such as the consumption of chlorine dioxide [36].…”
Section: Factors Associated With Chlorine Dioxide Consumptionmentioning
confidence: 99%
“…Ethnic differences in the prevalence of RE may be related to disparities in access to healthcare services, which in turn could be due to remoteness of location, discrimination, mistreatment and language boundaries. 10 , 28 , 29 Moreover, the access to and utilization of eye care services in lower socioeconomic status constituted a neglected public concern. Therefore, as discussed previously, the vast majority of members of ethnic minority groups have a low socioeconomic status, which forms a barrier to the access to and utilization of eye care services.…”
Section: Discussionmentioning
confidence: 99%
“…No Peru, levando em conta a diversidade cultural e étnica do país, Valenzuela-Oré e colaboradores 34 abordam a temática social do uso de PM. Aplicaram-se questionários a 775 povoados urbanos e rurais, sendo que 68,7% dos entrevistados relataram sempre usar PM 34 . No entanto, nota-se diminuição no uso da medicina tradicional na população peruana 35 .…”
Section: Usuários De Pm Na Aps: Perfil E Fatores Que Levam Ao Usounclassified